Variação linguística ao longo da vida em situação de contato dialetal : a variação do rótico em coda e das oclusivas dentais em ataque - Collet, Vanessa Adriana (2020)
This work, characterized as a case study, seeks to investigate the speech of an adult woman, born in Jundiaí-SP, with a history of migration to São Paulo-SP, Florianópolis-SC and Porto Alegre-RS over a period of 16 years, from 1994 to 2010. The sample under analysis is part of the VARSUL database and presents 205 minutes of informant's speech in personal experience interviews, referring to the years 1994, 1995, 1996, 2000, 2001 and 2010, in which she figures as an interviewer. Two linguistic variables are investigated in light of the theoretical-methodological assumptions of Variationist Sociolinguistics (LABOV, 1972, 1994), with emphasis on Dialects in Contact (TRUDGILL, 1986; CHAMBERS, 1992; SIEGEL, 2010) and Linguistic Change across Lifespan (SANKOFF e BLONDEAU, 2007; BAXTER e CROFT, 2016; SANKOFF, 2018): the production of the rotic in coda position and the plosives / t, d / in onset position. With the aid of the Rbrul tool (version 3.6.0), the linguistic and social variables that condition the production of the retroflex variant and the dental plosive variant, characteristics of the participant's maternal variety, are identified. The statistical results show, in general, a higher incidence of the tap variant in coda position over the 16 years, but with signs of revitalization of the retroflex variant. Regarding the conditioning of the retroflex variant, the variables year, previous context, following context and stress are statistically relevant. With regard to / t, d / variable in onset position, the statistical results show the predominance of the palate-alveolar affricate variant, with decreasing production of the dental variant, statistically conditioned by voicing, precedent context, following context, vowel status, stress and word class.